Searches for B meson decays to □, □ρ, □f0(980), and f0(980)f0(980) final states - Aubert, B; Bona, M; Karyotakis, Y; Lees, J; Poireau, V; Prencipe, E; Prudent, X; Tisserand, V; Garra Tico, J; Grauges, E; Lopez, L; Palano, A; et al. (2008)
We present the results of searches for B decays to charmless final states involving □, f0(980), and charged or neutral ρ mesons. The data sample corresponds to 384×106 BB̄ pairs collected with the BABAR detector operating at the PEP-II asymmetric-energy e+e- collider at SLAC. We find no significant signals and determine the following 90% confidence level upper limits on the branching fractions, including systematic uncertainties: B(B0→□)<2.0×10-7, B(B+→□ρ+)<30×10-7, B(B0→□ρ0)<3.3×10-7, B[B0→□f0(980)] ×B[f0(980)→π+π-]<3.8×10-7, and B[B0→f0(980) f0(980)]×B[f0(980)→π+π-]×B[f0(980)→K+K-]<2. 3×10-7. © 2008 The American Physical Society.